2007
DOI: 10.1523/jneurosci.3280-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Recombinant Adeno-Associated Virus-Mediated Neuropeptide Y Overexpression in the Hypothalamic Paraventricular Nucleus and Lateral Hypothalamus on Feeding Behavior

Abstract: It is well known that neuropeptide Y (NPY) increases food intake. The hypothalamic paraventricular nucleus (PVN) and the lateral hypothalamus (LH) are both involved in the acute, hyperphagic effects of NPY. Although it is obvious that increased energy intake may lead to obesity, it is less understood which aspects of feeding behavior are affected and whether one or multiple neural sites mediate the effects of long-term increased NPY signaling. By long-term overexpressing NPY in either the PVN or the LH, we unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 39 publications
6
52
1
Order By: Relevance
“…Levels of hypothalamic NPY are indicative of nutritional status; NPY mRNA content and NPY release increase during fasting and decrease after refeeding (Sanacora et al, 1990;Swart et al, 2001Swart et al, , 2002. Furthermore, increased NPY levels precede hyperphagia (Brady et al, 1990;Sahu et al, 1997;Tiesjema et al, 2007Tiesjema et al, , 2009. Direct pharmacological evidence of the orexigenic effects of NPY are provided by studies demonstrating that its intracerebroventricular administration (Clark et al, 1984;Levine and Morley, 1984;Semjonous et al, 2009) or its direct administration into FIG.…”
Section: Arcuate Nucleus Orexigenic Neuropeptide Y/agouti-related Pepmentioning
confidence: 99%
“…Levels of hypothalamic NPY are indicative of nutritional status; NPY mRNA content and NPY release increase during fasting and decrease after refeeding (Sanacora et al, 1990;Swart et al, 2001Swart et al, , 2002. Furthermore, increased NPY levels precede hyperphagia (Brady et al, 1990;Sahu et al, 1997;Tiesjema et al, 2007Tiesjema et al, , 2009. Direct pharmacological evidence of the orexigenic effects of NPY are provided by studies demonstrating that its intracerebroventricular administration (Clark et al, 1984;Levine and Morley, 1984;Semjonous et al, 2009) or its direct administration into FIG.…”
Section: Arcuate Nucleus Orexigenic Neuropeptide Y/agouti-related Pepmentioning
confidence: 99%
“…We investigated whether knockdown of Socs3 mRNA in the MBH had any effects on mRNA expression levels of Agrp, Npy, and Pomc, because leptin signaling is suggested to regulate transcription of these neuropeptides. In addition, the observed phenotype, reduced locomotor activity, and increased feeding in the light phase resemble that of increased NPY signaling (Tiesjema et al 2007). Radioactive ISH showed that AAV-sh-1 rats had significantly increased levels of Npy in the Arc compared with AAV-sh-c rats (Fig.…”
Section: Effects Of Socs3 Knockdown On Endocrine Parameters and Body mentioning
confidence: 83%
“…The increased levels of Npy mRNA that we observed may explain the unexpected effects on body weight, food intake, fat mass, and locomotor activity after Socs3 knockdown in the MBH. Viral vector-mediated Npy overexpression in several hypothalamic regions results in increased body weight, decreased locomotor activity in the dark period, and increased food intake, in particular, in the light period (Tiesjema et al 2007, Yang et al 2009). In addition, acute i.c.v.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations